2016
DOI: 10.17356/ieejsp.v2i2.183
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Democracy in an Era of Free Markets: Karl Polanyi’s Perspectives on the Politics of Finance

Abstract: With the contemporary crisis of liberal democracy and the rise of illiberalism in the aftermath of the global financial crisis we are witnessing a renewed interest in structuralist theories that conceptualize the inherent tensions of modernization, crises and democracy. In my paper I attempt to show that Polanyi's thinking represents such a framework that can be updated to fit contemporary realities both in core and peripheral countries. After the introduction I reconstruct Polanyi's political stance regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…By contrast, financialization in EMEs is usually framed around geopolitical dependency and risk, ignoring the active role of the state (Becker et al, 2010;Bortz and Kaltenbrunner, 2017;Botta et al, 2014;Karwowski and Stockhammer, 2017;Scheiring, 2016). While there is ample evidence for the negative consequences of financialization in EMEs, two misconceptions should be avoided: one is that it is simply externally imposed on EMEs.…”
Section: The State-financialization Nexus In Emesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, financialization in EMEs is usually framed around geopolitical dependency and risk, ignoring the active role of the state (Becker et al, 2010;Bortz and Kaltenbrunner, 2017;Botta et al, 2014;Karwowski and Stockhammer, 2017;Scheiring, 2016). While there is ample evidence for the negative consequences of financialization in EMEs, two misconceptions should be avoided: one is that it is simply externally imposed on EMEs.…”
Section: The State-financialization Nexus In Emesmentioning
confidence: 99%
“…The case study approach is justified given the paradigmatic nature of Hungary as one of the most striking examples of an export-led EME, where hegemonic neoliberalism gave way to an ASC regime after the GFC, leaving open the debate as to whether financialized neoliberalism was displaced or coopted. Furthermore, Hungary is consensually analysed through the prism of dependency (Bohle and Greskovits, 2012;E ´ber et al, 2019;N€ olke and Vliegenhart, 2009), making it an ideal candidate for studying dependent financialization (Bonizzi et al, 2020;Bortz and Kaltenbrunner, 2017;Scheiring, 2016). This paper aims to qualify the temptation to equate subordinate positions in global trade and financial networks with a lack of domestic political agency in EMEs, recovering the strategic role of the state in finetuning different dimensions of financialization for political purposes.…”
Section: Introductionmentioning
confidence: 99%
“…To grasp the linkages between global economic transformations and the rise of illiberalism, the article starts with Karl Polanyi’s concepts of (dis)embedding, commodification and countermovement (Polanyi, 2001 [1944]). Scholars have convincingly shown that Polanyi’s theory can be adapted to the context of contemporary financialised capitalism on Europe’s Eastern periphery to highlight how postsocialist dependent development strained livelihoods, social relations and cultural imaginaries in specific locales (see Bohle and Greskovits, 2012; Hann, 2019; Scheiring, 2016; Szombati, 2018b).…”
Section: The Political Economy Of Authoritarian Re-embeddingmentioning
confidence: 99%
“…266). Analyzing the cataclysm of market societies in the 1930s, Polanyi was convinced that within a framework of 'One Big Market', with universal money facilitating the exchange of everything, democracy could not be sustained (Scheiring, 2016). Today again, selective restrictions on finance, trade and investmentespecially restraining financial markets by means of capital controls and abandoning a legal framework that privileges privatization and capital globally (Pistor, 2019) are a prerequisite for flourishing foundational economies and democracy.…”
Section: Liberal Globalismmentioning
confidence: 99%